Cultural Lag in the Digital Transformation of Health Services: An Observational Study at Nunukan Timur Public Health Center - Ana Welellu; Arlin Adam; Andi Alim (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Digital transformation in health services faces significant challenges, particularly the gap between rapid technological advancements and the readiness of institutional work culture. This study investigates the cultural lag experienced during the implementation of digital systems at the East Nunukan Health Center. Using an observational qualitative approach, it examines health workers' responses to digital applications such as e-Puskesmas and various Health Information Systems. The findings reveal substantial resistance to change, attributed to factors like limited digital literacy, inadequate infrastructure, and the persistence of traditional work patterns. Despite the introduction of digital systems, healthcare practices remain largely dependent on manual methods, highlighting the disconnect between technological progress and the socio-cultural preparedness of healthcare organizations. The study concludes that this cultural lag within healthcare institutions can significantly impede the effectiveness of digital transformation efforts. To address these issues, the research advocates for ongoing training, improvement of supporting facilities, and the adoption of strategies that align with local work culture. This research provides valuable insights into the socio-cultural dynamics affecting the digitization of public services, especially in border regions with limited technological access.